Real‐time mobile teledermoscopy for skin cancer screening targeting an agricultural population: an experiment on 289 patients in France. (16th November 2015) - Hue, L.; Makhloufi, S.; Sall N'Diaye, P.; Blanchet‐Bardon, C.; Sulimovic, L.; Pomykala, F.; Colomb, M.; Baccard, M.; Lassau, F.; Reuter, G.; Keller, F.; Fite, C.; et al.
Abstract: Background: The incidence of skin cancer has reached epidemic proportions in the white population and is significantly elevated in agricultural populations, who are exposed to ultraviolet radiation during their professional activities. In 2014, the Agricultural Social Insurance Mutual Benefit Fund (MSA) offered its customers who work in agriculture and live in rural areas with reduced access to dermatologists the ability to participate in a 1‐day teledermoscopic (TDS) screening event. Objective: This study's aim was to assess the feasibility of real‐time mobile TDS triage of a large number of agricultural workers by trained medical officers and occupational physicians. Methods: Fifteen TDS screening centres were located in different areas of France. Individuals older than 18 years who worked in agriculture and lived in rural area near a TDS screening centre were invited to participate in a 1‐day screening event and were examined by an MSA physician. In cases of suspicious skin lesions, clinical and dermoscopic images were obtained and transferred immediately to four dermatologists who were simultaneously present at the tele‐platform for diagnosis and decision‐making. Low‐quality images were retaken. Results: Two‐hundred eighty‐nine patients underwent skin cancer screening. Among 199 patients (69%), 390 suspicious lesions were identified and generated 412 pictures. All lesions were analysed by dermatologists. For 105 patients (53%), no follow‐up was required. Seventeen patients were referred to local dermatologists for rapid examination, including 12 cases of suspected malignant melanocytic lesions. Among the 12 patients with suspected melanoma, face‐to‐face visits were conducted within 10 days for 11 of them, and 1 case of melanoma was confirmed by histopathology. Conclusions: Our study suggests that teledermoscopy performed in the context of occupational medicine and targeted to agricultural populations is feasible and could be useful for improving skin cancer screening in at‐risk populations while avoiding face‐to‐face examinations by a dermatologist in 53% of cases.